1987
DOI: 10.1111/j.1439-0442.1987.tb00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Xylazine‐Induced Hyperglycaemia and α‐Adrenergic Receptors in Sheep

Abstract: Intravenous injection of the a-adrenergic receptors agonist xylazine (0.3 mg/kg b. w.) produced hyperglycaemia with its peak (1 10 mg/100 ml) 30 min later in sheep. This hyperglycaemia was statistically significant for 3 hours. When xylazine was administered after pretreatment of the animals with either the a,-adrenergic receptors blocker prazosin (0.5 mg/kg i. v.) or the a2-blocker yohimbine (0.5 mg/kg i. v.) a hyperglycaemia was also produced but in the case of prazosin its peak did not exceed 95 mg/100 ml, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 5 publications
(1 reference statement)
3
11
1
Order By: Relevance
“…In previous studies, administration of xylazine HCl to sheep led to an increase in serum glucose concentration (1,22). The results of the present study support previous findings in that xylazine HCl continued to produce a hyperglycaemic effect for a period of at least 120 min following its administration.…”
Section: Resultssupporting
confidence: 91%
“…In previous studies, administration of xylazine HCl to sheep led to an increase in serum glucose concentration (1,22). The results of the present study support previous findings in that xylazine HCl continued to produce a hyperglycaemic effect for a period of at least 120 min following its administration.…”
Section: Resultssupporting
confidence: 91%
“…There have been many investigations into the hyperglycaemic effect of xylazine (Eichner et al, 1979;Hsu and Hummel, 1981;Brikas et al, 1987) and medetomidine (Cullen, 1996). Hyperglycaemia may be due to α 2 -adrenergic inhibition of insulin release by stimulation of α 2 -receptors in the pancreatic β-cells (Angel and Langer, 1988) and to increased glucose production in the liver (Hsu and Hummel, 1981).…”
Section: Discussionmentioning
confidence: 97%
“…O n the other hand, Hsu and HUMMEL (1981) showed that xylazine caused both a2and a ] -agonistic effects on the cardiovascular system in dogs. BRIKAS et al (1987), working on xylazine induced hyperglycaemia in sheep, also suggested that this drug showed both a2and a,-agonistic properties. So, the involvement of the a2adrenoreceptors in the regulation of sheep reticulo-ruminal phasic motility was studied in the present work using the fairly selective a*-agonist naphazoline (LEES, 1981).…”
Section: Discussionmentioning
confidence: 99%